2006
DOI: 10.1124/jpet.106.104158
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1-Dependent and -Independent Regulation of Insulin-Like Growth Factor-1-Stimulated Vascular Endothelial Growth Factor Secretion

Abstract: Hypoxia-induced stress plays a central role in retinal vascular disease and cancer. Increased hypoxia-inducible factor-1␣

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 38 publications
3
48
0
1
Order By: Relevance
“…While tumor cells express VEGF necessary for the chemotaxis of endothelial cells into the growing tumor tissue, the process of wound angiogenesis is dependent on endogenously expressed VEGF produced by various cells, including macrophages and keratinocytes [13,27]. Thus, inactivation of Akt causes inhibition of VEGF expression as has been reported by several groups [29,33,38,41]. In turn, reduced VEGF levels seem to be responsible for defective angiogenesis in wounds of Akt1 -/-mice.…”
Section: Discussionmentioning
confidence: 80%
“…While tumor cells express VEGF necessary for the chemotaxis of endothelial cells into the growing tumor tissue, the process of wound angiogenesis is dependent on endogenously expressed VEGF produced by various cells, including macrophages and keratinocytes [13,27]. Thus, inactivation of Akt causes inhibition of VEGF expression as has been reported by several groups [29,33,38,41]. In turn, reduced VEGF levels seem to be responsible for defective angiogenesis in wounds of Akt1 -/-mice.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, however, Mark et al reported that IGF-I treatment led to increased HIF-1α mRNA levels in the retinal pigment epithelium (RPE) cells ARPE-19 [5] . In the present study, IGF-I did not obviously up-regulate HIF-1α mRNA levels in MCF-7 cells ( Figure 2C).…”
Section: Discussionmentioning
confidence: 99%
“…We wondered whether the tube formation was induced by IGF-I directly or by other genes. Previous studies have demonstrated that IGF-I can enhance the expression of VEGF [5][6][7][8] , which plays a central role in the process of angiogenesis. Our results also showed that IGF-I induced VEGF expression and transcriptional activation (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in detail above, IGFs promote endothelial cell migration and tube formation in vitro. IGF1 and IGF2 stimulate HIF1A expression (Hoeben et al 2004), and IGF1 induces VEGF synthesis (Warren et al 1996, Stearns et al 2005) via HIF1-dependent andindependent pathways (Slomiany & Rosenzweig 2006). IGF2 also plays a role in angiogenesis (Wang et al 1998, Kim et al 2012, at least in part by inducing VEGF synthesis (Hoeben et al 2004 IGFs are involved in early vascular development.…”
Section: Insulin-like Growth Factorsmentioning
confidence: 99%